Association of serum allopregnanolone with restricted and repetitive behaviors in adult males with autism. (January 2021) - Chew, Leila; Sun, Kevin L.; Sun, Wenchao; Wang, Zhe; Rajadas, Jayakumar; Flores, Ryan E.; Arnold, Emily; Jo, Booil; Fung, Lawrence K.
Highlights: Serum allopregnanolone levels in adult males with ASD are non-normally distributed. Lower allopregnanolone levels correlate with more severe repetitive behaviors. Lower allopregnanolone levels correlate with less insight into behavioral severity. Abstract: Autism spectrum disorder (ASD) has been associated with imbalance between excitatory and inhibitory (E/I) neurotransmission systems, as well as with neuroinflammation. Sitting at the crossroads between E/I imbalance and neuroinflammation is a class of endogenous hormones known as neurosteroids. Current literature points to dysregulated steroid metabolism and atypical neurosteroid levels in ASD as early as in utero . However, due to the complexity of neurosteroid metabolomics, including possible sex differences, the impact of neurosteroids on ASD symptomatology remains unclear. In this study, we assessed neurosteroid levels and ASD symptom severity of 21 males with ASD and 20 full-scale-IQ-matched typically developing (TD) males, all aged 18–39. Using liquid chromatography-tandem mass spectrometry, concentrations of allopregnanolone, cortisol, dehydroepiandrosterone, progesterone, and testosterone were measured in saliva and serum. With the exception of cortisol's, all neurosteroids' concentrations were found to have ASD vs. TD group differences in distribution, where one group was normally distributed and the other non-normally distributed. Serum allopregnanolone levels in males with ASD were found to negatively correlate with clinician-rated measures of restricted and repetitive behavior measures (ADOS-2 RRB and ADI-R RRSB domain scores). Additionally, lower serum allopregnanolone levels were found to predict more negative camouflaging scores, which represent greater differences in self- and clinician-rated symptom severity, of both ASD symptomatology overall and repetitive behaviors in particular. Taken together, our findings demonstrate that in adult males with ASD, decreased serum allopregnanolone levels are associated with more severe restricted and repetitive behaviors and with less insight into the severity of these behaviors.